1992
DOI: 10.1126/science.1604323
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Stimulation of the Ras-Guanine Nucleotide Exchange Factor and GAP Activities

Abstract: The biological activity of Ras proteins is thought to be controlled by the guanine nucleotide exchange factor and the guanosine triphosphatase activating protein (GAP). Treatment of rat pheochromocytoma PC-12 cells with nerve growth factor (NGF) increased the amount of active Ras guanosine triphosphate complex and stimulated the activities of both the guanine nucleotide exchange factor and GAP. In PC-12 cells that overexpressed the tyrosine kinase encoded by the trk proto-oncogene (a component of the high-affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 32 publications
4
56
0
1
Order By: Relevance
“…[ 3 H]GDP -Rac1 complexes were prepared by incubating GST -Rac1 with [ 3 H]GDP. GDP -GTP exchange assay was performed by filter binding assay as described (Li et al, 1992).…”
Section: Guanine Nucleotide Exchange Assaymentioning
confidence: 99%
“…[ 3 H]GDP -Rac1 complexes were prepared by incubating GST -Rac1 with [ 3 H]GDP. GDP -GTP exchange assay was performed by filter binding assay as described (Li et al, 1992).…”
Section: Guanine Nucleotide Exchange Assaymentioning
confidence: 99%
“…Ras proteins can be activated in response to a wide variety of mitogenic or activation stimuli (Avruch et al, 1994;McCormick, 1994), and suppression of Ras activity using either dominantnegative mutants of Ras or neutralizing anti-Ras antibodies efficiently blocks entry of cells into S-phase after growth factor stimulation (Moodie et al, 1993;Khosravi-Far and Der, 1994;Winston et al, 1996). Recently, many studies have suggested that expression of oncogenic Ras may be associated with multiple genetic alterations which contribute to initiation of abnormal karyotype, deregulation of cell growth, development of cancer, and perhaps susceptibility to apoptosis (Hirakawa and Ruley, 1988;Li et al, 1992;de Vries et al, 1993;Denko et al, 1994;Arber et al, 1996;Chen and Faller, 1996;Chen, et al, 1998). However, the mechanisms by which oncogenic Ras induces these seemingly disparate genetic alterations remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Ras proteins have been found to be involved in the regulation of many cellular biological or pathological processes, such as proliferation and differentiation, as well as apoptosis (Barbacid, 1987;Bourne et al, 1990;Downward et al, 1990;Li et al, 1992;Marshall, 1993;Faller, 1995, 1996). Although the direct targets of Ras proteins are not entirely defined, many downstream effectors of the Ras signaling pathway have been suggested (Hattori et al, 1992;Zhang et al, 1992;Buday and Downward, 1993;Medema et al, 1993;Votjtek et al, 1993;Harrington et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Ligand binding to such receptors stimulates ras guanine-nucleotide exchange activity (32)(33)(34)(35)(36) and increases the level of GTP-bound ras (37,38). Whether EGF acts also through inhibition of the Rb gene has not been reported.…”
Section: Discussionmentioning
confidence: 99%